Parental Involvement in Islamic Religious Education and its Effect on Students' Religious Discipline in Junior High School - Nadia Oktavia (Yayasan Bayt Shufiya Nusantara, 2024)
This study aims to analyze the effect of parental involvement in Islamic religious education on students' religious discipline at YASPEN Cerdas Bangsa Junior High School, Sudi Rejo, Namorambe District, Deli Serdang Regency, North Sumatra. This research uses a quantitative approach with a correlational method. The research sample amounted to 40 students who were selected by total sampling. Data were collected through a closed questionnaire which was arranged based on indicators of parental involvement and indicators of student religious discipline. The results of the analysis show that the level of parental involvement in Islamic Religious Education is in the good category, while students' religious discipline is classified as very good. The correlation coefficient (rxy) obtained is 0.425, which is higher than the rt value at the 5% (0.312) and 1% (0.403) significance levels. Thus, there is a positive and significant relationship between parental involvement in Islamic education and students' religious discipline. This study confirms the importance of the active role of parents in fostering children's religious education as a foundation for the formation of religious character and disciplinary attitudes in the school environment.